Electric motor propulsion system for electric vehicles (EV) - Roslan, Ahmad Faiz (2008)
In a bid to perform electric vehicle modeling in terms of propulsion system of the electric motor, the calculation and the analysis of vehicles dynamics have been done. Its will concluded the suitable motor that will used to move the specific vehicles, ISWARA. Through the literature review, this thesis presented the introduction of electric vehicles and the major components of its system. Besides that, it will discuss the propulsion system for electric motor of the electric vehicles. Next, calculation and analysis been done to find the requirement power and force to move the vehicle in fixed velocity. Results get from the calculation will be used to find the characteristics of electric motor and finally the suitable electric motor are selected. Simulation done to analysis the suitable motor either it can perform and give the similar results compare to calculation made before or not. At the end of this thesis, conclusion is made due to the results get from the simulation analysis. Recommendation in improving the results from whole of the project will also be discuss.